中國文化視野中的人與動物關係問題——以異種移植為例: The Issue of Human-to-animal Relationship from a Chinese Perspective: The Case of Xenotransplantation - LEI, Ruipeng (International Journal of Chinese & Comparative Philosophy of Medicine, 2007)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 在不同的文化中，關於如何對待動物是可接受的或者說人與動物的關係問題存在各種不同的觀點。本文主要從中國文化的視角來討論和分析這一倫理問題，梳理儒釋道三種思想體系中所包含的生態倫理思想，分析它們對人與動物關係問題的態度，尤其是對異種移植中使用動物問題的倫理論證的有益啟示。從儒家的視角，以貫穿儒家理論與實踐體系的仁愛思想為主線，揭示出由親而疏、由近及遠地踐行“仁”，是完善和提升人性的必要途徑，也是實現普遍的愛的現實的人類行動方式。儒家強調“愛物”的美德， 但不排斥在得到倫理辯護的基礎上使用動物﹔從佛家的視角，以“不殺生”的戒律和“十界論”的生命觀為基礎， 闡明佛家哲學對動物生命的絕對尊重與保護﹔從道家的視角，以“道法自然”和“ 厚德載物”思想為線索，釐清道家哲學崇尚自然、順乎自然的中心思想，以及對不干預自然秩序的強調。 In different cultures there is a spectrnm of opinions regarding what it is acceptable to do to animals, including whether it is morally acceptable or not to use them as a source of organs or tissues for transplants. This essay attempts to discuss these ethical issues in the Chinese cultural context. Chinese culture is primarily the combination of Confucianism, Buddhism and Taoism. There are diverse attitudes towards nature and differing views about the relationship of humans to animals. Confucianism emphasizes the principle of ren (benevolence) and demonstrates that the method of practicing ren is from near to far, from parents/siblings to other relatives, friends, co-workers, neighbors, patients, students etc, from present generation to future generations, from human beings to other animals, plants and eco-system or nature as a whole. On the other hand, Confucianism holds that humanity is most valuable in the world, certainly of a higher order than that of animals. These views would be compatible with the limited use of animals in medical procedures where the benefit to humans is clear, demonstrable and large. Buddhism emphasizes simple, non-violent, gentle living. Its first precept involves abstention from injury to life, and not depriving a living being of life. These views may entail a direct prohibition on the use of animals for medical purpose. Taoism places the harmony between human beings and nature in general in high esteem. It recognizes that human beings are not separate from nature but a small part of the natural world. Human beings should not seek to dominate or interfere with nature, but should instead stand in a relationship of care and concern for its continued flourishing. Accordingly, Daoism might regard any form of xenotransplantation as an unacceptable intervention with nature. DOWNLOAD HISTORY | This article has been downloaded 239 times in Digital Commons before migrating into this platform.